2017
DOI: 10.1177/1356336x16683898
|View full text |Cite
|
Sign up to set email alerts
|

‘Drawing’ conclusions

Abstract: This study explores the relationship between primary school physical education and physical activity as sites for the practice of physical activity of Irish primary school children. Understanding how children make connections between physical activity sites is important in shaping physical education experiences that promote lifelong participation. Children’s (aged 8–11) awareness, knowledge, and understanding of physical activity and physical education were examined using participatory methods of ‘draw and wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Drawing has been used as a research tool across many fields for understanding perception and mental models, particularly in education [45] and health [21,26,35]. Drawings have been used to study abstract phenomena such as celebrity [18], energy [5], and information [23].…”
Section: Visual Analysismentioning
confidence: 99%
“…Drawing has been used as a research tool across many fields for understanding perception and mental models, particularly in education [45] and health [21,26,35]. Drawings have been used to study abstract phenomena such as celebrity [18], energy [5], and information [23].…”
Section: Visual Analysismentioning
confidence: 99%
“…Pendidikan jasmani juga merupakan tempat belajar, kesempatan untuk belajar permainan baru, teknik olahraga, dan melakukan aktivitas gerak (Parker, MacPhail, O'Sullivan, Chróinín, & McEvoy, 2018). Anak-anak melihat bahwa 'melakukan' pendidikan jasmani di sekolah adalah tentang mempelajari bagaimana menjadi aktif secara fisik, terlepas dari kenyataan bahwa anak-anak memahami upaya guru dan pelatih sebagai peluang untuk belajar berlari, melompat, dan melempar dengan lebih baik.…”
unclassified
“…The participants identified the importance of authentic relationships with students, this could foster a working alliance through the development of tripartite agency ( 34 ) leading to positive valuation of the PE classes ( 37 ). Children have identified that being engaged in a competency progression (i.e., learning something new) is fun ( 42 ) and upon reflection these children would associate enjoyment with the class leading to increased likelihood of lifelong participation in movement ( 14 , 43 ). Through the intentional construction of positive challenges using physical literacy in PE, participants also suggested this supported student engagement, motivation, and continued participation within their PE classes.…”
Section: Discussionmentioning
confidence: 99%